PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL EXPERIENTIAL LEARNING DENGAN PENDEKATAN KONSTRUKTIVISME DI SMA NEGERI 2 TONDANO - Heldi Angelia Gavrilla Ngkunda; Tineke Makahinda; Djeli Alvi Tulandi (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to develop leatning tools based on experiential learning models with constructivistapproach so as to produce valid, practical and effective learning tools that can improve learningprocesses and outcomes in the material of momentum and impulse in class X B students of SMA Negeri2 Tondano. The learning tools produced are teaching modules, teaching materials and StudentWorksheets. The type of research used in this research is development research with the 4D researchmodel, namely define, design, development and disseminate. The results of this study are: (1) theresulting device is "Valid" and can be used without revision; (2) the resulting device is practically basedon the percentage results for the implementation of learning which is 94.9% and the results of thestudent response questionnaire stating that the learning process with the experiential learning modelwith a constructivism approach is practically used in class; (3) the resulting device is effective as seenfrom the acquisition of an N-Gain score of 0.7 with the "Moderate" criterion, the results of learningattitudes obtain an average percentage of 80.33, the results of learning skills obtain an averagepercentage of 78.48 both have "Good" criteria, and student process assessment with 73.79% (P1) and84.49% (P2) with an average process of 79.14% with "Good" criteria. From the acquisition of learningoutcomes and comparison of process assessment values (P1) & (P2) it is concluded that there is anincrease in learning outcomes and processes for students using the resulting learning tools.